Hubungan Perilaku Masyarakat Dengan Kepatuhan Penerapan Protokol Kesehatan Di Masa Pandemi Covid-19 - Sukmawati Dewi (2021)
The COVID-19 pandemic has been declared since March 11, 2020 by WHO. The Government of the Republic of Indonesia has issued a health protocol that is implemented throughout Indonesia and is centrally guided by the Ministry of Health of the Republic of Indonesia. This study aims to determine the relationship between community behavior and compliance with the application of health protocols during the Covid-19 pandemic. Sampling was done by means of propotional stratified simple random by adjusting the inclusion and exclusion criteria that have been set with a total sample of 230 samples. The data was collected by distributing questionnaires containing the behavior consisting of knowledge, attitudes and actions and a compliance questionnaire. Analysis of the data used is univariate and bivariate analysis. Univariate analysis is by looking at the percentage frequency distribution of each sub-variable characteristic of breastfeeding mothers. Bivariate analysis using Chi Square test. The results of the Chi Square analysis test show that the p-value of knowledge with compliance is 0.028, which means that there is a relationship between knowledge and compliance. The results of the analysis of attitudes with compliance show p-value = 0.004 which means that there is a relationship between attitude and compliance. The results of the analysis of actions with compliance show p-value = 0.009, which means that there is a relationship between action and compliance. The conclusion of this study is that there is a relationship between community behavior and compliance with the application of health protocols during the Covid-19 pandemic. Researchers suggest the public to increase their awareness in implementing health protocols such as applying hand washing, wearing masks and maintaining distance and staying away from crowds.